PEMANFAATAN STRATEGI PEMASARAN DIGITAL MENGGUNAKAN E-COMMERCE SHOPEE: DIGITAL MARKETING UTILIZATION STRATEGY USING SHOPEE E-COMMERCE - Sihombing, Ciska Debora; Afriani, Dwi; Supeno, Bambang (Komunitas Manajemen Kompetitif, 2023)
Meri Snack's is engaged in the food business, namely producing processed products made from cassava and potatoes to produce cassava chips, potato chips and opaque products with various flavors. Get permission from the P-IRT Health Office: 2111471010170-27. Digital marketing is carried out by utilizing the Shopee e-commerce platform. The research method is descriptive qualitative, through observation, interviews and documentation. The results of research activities at Meri Snack's are that an e-commerce platform has been created which is expected to be able to use it as much as possible so that it can expand sales reach, increase consumers, increase sales and its products are known by the wider community and create more creative content about selling Meri Snack's products.